Accumulation Pattern of Flavonoids in Cabernet Sauvignon Grapes Grown in a Low-Latitude and High-Altitude Region - Xing, Ran-Ran; He, Fei; Xiao, Hui-Lin; Duan, Chang-Qing; Pan, Qiu-Hong (South African Journal of Enology and Viticulture, 2016)
Particular climate conditions in a low-latitude and high-altitude region endow grape berries with distinctive quality characteristics. So far, few reports have been concerned with the formation of berry flavour in such a region. This study aimed to investigate the accumulation pattern of flavonoids in Vitis vinifera L. cv. Cabernet Sauvignon grape berries growing at different altitudes of the highland in southwest China in two consecutive vintages. In addition to the 3-O-monoglucosides and 3-O-acyl monoglucosides of the five main anthocyanidins (delphinidin, cyanidin, peonidin, petunidin and malvidin), some uncommon anthocyanins, such as three diglucosides of anthocyanidins and pelargonidin-3-O-glucoside, were detected in the grape berries. Higher altitude cultivation greatly promoted the production of anthocyanins and flavonols, particularly cyanidintype anthocyanins and quercetin-type flavonols from the F3’H branch of the flavonoid biosynthetic pathway. Flavan-3-ols from both branches were comparatively less influenced by vineyard altitude. Vintage in this high-altitude region also had a dramatic influence on the accumulation of flavonoids. Most of the anthocyanin and flavonol components were affected more by vineyard altitude than by vintage, whereas the accumulation of flavan-3-ols differed mainly between vintages. The present data will not only improve the understanding of flavonoid accumulation in grapes from a high-altitude region with different climates, but also provide practical guidance for the production of high-quality grapes and wine.